(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The present work is focused on the preparation and in vitro release kinetics of liposomal formulation of Leuprolide Acetate. In this work, “Thin Lipid Film Hydration Method” was used for preparation of Leuprolide Acetate loaded liposomes. Prepared liposomal formulations of Leuprolide acetate was evaluated by drug entrapment study, in-vitro drug release kinetics and stability studies. The percentage drug entrapment of Leuprolide acetate for F1 and F2 formulations were found to be 78.14 ± 0.67 and 66.70 ± 0.81% respectively. In-vitro drug release study of liposomal formulations had shown zero order release pattern. Regression co-efficient (R2) value of Zero order kinetics for F1 and F2 formulations were 0.9912 and 0.9676 respectively. After storing formulations for 1 month, stability testing was done at 40C.It was found that all batches were stable. These liposomal formulations of Leuprolide acetate can be formulated for parenteral application to treat prostate cancer and in women, to treat symptoms of endometriosis (overgrowth of uterine lining outside of the uterus) or uterine fibroids.